2021
DOI: 10.3389/fimmu.2021.736692
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Are Identified in the Lung Parenchyma of Wild Mice, Which Can Be Recapitulated in Naturalized Laboratory Mice

Abstract: BackgroundIt is well documented that laboratory mice bred and maintained in ultra-hygienic specific pathogen-free (SPF) barriers display reduced richness and complexity of microbiota compared with wild mice. The laboratory mice profoundly lack lung parenchymal mast cells. Hence, we aimed to investigate the lung distribution of mast cells in free-living wild mice.MethodsWild house mice were trapped in South-Eastern Norway and Hemtabad, West Bengal, India. C57BL/6 laboratory mice were bred in a purposefully buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…These include: (i) introducing fecal matter from wild mice to GF mice by oral gavage; 112 (ii) transferring embryos from lab mice to wild surrogate dams to generate "wildlings"; 111 (iii) "re-wilding" laboratory mice by housing them in an outside enclosure that recapitulates the habitat of wild mice; 122 or (iv) housing them with bedding from their natural environment. 123 Each approach results in genetically identical laboratory mice with wild microbiomes that can be stably transferred and maintained over generations, thus facilitating microbiome diversification while preventing confounding results from genetic variability. Although similar, their resulting microbiomes may not fully converge with those of wild mice, as has been described for wildlings, 111 possibly due to differences in host genomes and diets.…”
Section: Human Microbiota-associated Mouse Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include: (i) introducing fecal matter from wild mice to GF mice by oral gavage; 112 (ii) transferring embryos from lab mice to wild surrogate dams to generate "wildlings"; 111 (iii) "re-wilding" laboratory mice by housing them in an outside enclosure that recapitulates the habitat of wild mice; 122 or (iv) housing them with bedding from their natural environment. 123 Each approach results in genetically identical laboratory mice with wild microbiomes that can be stably transferred and maintained over generations, thus facilitating microbiome diversification while preventing confounding results from genetic variability. Although similar, their resulting microbiomes may not fully converge with those of wild mice, as has been described for wildlings, 111 possibly due to differences in host genomes and diets.…”
Section: Human Microbiota-associated Mouse Modelsmentioning
confidence: 99%
“…It is possible that these differences are sufficient to shape the local innate immune cell landscape, as mast cells are enriched in the lung parenchyma of wild but not SPF mice. 123 Yeh et al found that housing SPF mice in a semi-natural environment consisting of farmhouse-sourced bedding was sufficient to increase mast cell recruitment to the lung. 123 Although environmental components played a role in driving this phenotype, microbial communities present in the mice, or the bedding were not characterized in this study.…”
Section: Human Microbiota-associated Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For some of the PCA assays, Evans blue was obviated and ear tissues were sectioned and analyzed with toluidine blue staining for revealing mast cell morphology as previously described [18]. Or alternatively, the ear sections were processed for histamine analysis as previously described [19]. Brie y, the sections were incubated with the rabbit anti-histamine antibody (Fine Test, Wuhan, China), and then with horseradish peroxidase-linked anti-rabbit and anti-mouse universal secondary antibodies (Solarbio, Beijing, China).…”
Section: Passive Cutaneous Anaphylaxis Assaymentioning
confidence: 99%
“…Other than being highly expressed on mast cells, CD117 is expressed on interstitial Cajal cells of the intestine and melanocytes of the skin . However, CD117 is reported to be expressed at very low levels in the lungs , suggesting that the strong luminescence signal in the lungs is a result of nonspecific binding from the antibody. Further work is needed to identify the specific cell type that is being transfected in the lungs and whether there is a specific receptor that is interacting with the antibody.…”
mentioning
confidence: 99%